The Value of Quantitative Ultrasound Elastography in the Assessment of Non-Alcoholic Fatty Liver Disease in Children - Cao, Xu; Liu, Jianbo; Li, Jing; Shi, Kexin; Zheng, Shuang; Di, Dongna; Tian, Peng (Current Medical Imaging, 2025)
ObjectiveThis preliminary investigation aimed to assess the value of two elastography techniques, sound touch elastography (STE) and sound touch quantification (STQ), in measuring liver stiffness in children with non-fatty versus fatty livers.MethodsThis study used a case-control design. The STE and STQ were used to measure and compare liver stiffness in 121 children with fatty livers and 251 children with non-fatty livers, respectively.ResultsIn this study, we found that, compared to children with non-fatty liver disease, children with fatty liver disease had lower Young's modulus values in STE and STQ in the left lobe of the liver, and the difference was statistically significant (P < 0.05). However, after multifactorial analysis, no association was found between liver Young's modulus values measured by STE and STQ and the presence of fatty liver in children.In the present study, significantly higher Young's modulus values were observed in the left lobe compared to the right lobe of the liver in children with non-fatty liver (P < 0.05). In contrast, no significant difference was found between the left and right lobes in children with fatty liver (P > 0.05). The optimal diagnostic threshold for detecting steatohepatitis in the left lobe was 5.890 kPa using STE and 8.050 kPa using STQ.ConclusionSTE and STQ, as the latest ultrasound diagnostic techniques based on shear wave elastography, can quantitatively assess fatty liver in children. In this study, some liver elasticity measurements in the fatty liver group differed from those in the non-fatty liver group.
Keywords: Fatty liver disease